Cost-Benefit Analysis in Sustainable Tourism: Best Practices and Policy Implications - Berisha, Vlora; Rayfield, Blake; Ramaj, Behrije; Beqiri, Theranda; Gashi, Altina; Mekuli, Mimoza (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Sustainable tourism is critical in driving economic growth, preserving the environment, and enhancing social well-being by minimizing negative impacts and maximizing long-term benefits. Cost-benefit analysis (CBA) is a vital tool for stakeholders and decision-makers to examine the feasibility and impacts of tourism projects by quantifying economic, environmental, and social factors. This study presents state-of-the-art practices in applying CBA to sustainable tourism and its use in assessing return on investment, employment, poverty reduction, biodiversity, and cultural heritage conservation. While CBA enhances decision-making, challenges remain in assessing non-market benefits and trade-offs between stakeholders. This paper synthesizes real-world applications and methodological advances and examines how CBA informs evidence-based sustainable tourism policy. Using Peja, Kosovo, as a case study, the paper identifies the need to integrate local economic, environmental, and cultural factors into QA frameworks to inform sustainable development.